DESIGN, DEVELOPMENT, AND EVALUATION OF AN ION-ACTIVATED OPHTHALMIC IN SITU GEL OF MOXIFLOXACIN HYDROCHLORIDE - KONDALKAR, GIRISH; DEV, ASISH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to develop an in situ ophthalmic gel of an anti-infective drug, moxifloxacin (MOX) hydrochloride (HCL), for sustained ocular delivery for the treatment of bacterial infections of the eye. Method: In the present work the in situ gelling systems were prepared by ion exchange method with the help of various concentrations of gelling agent gelrite (0.08 g, 0.1 g and 0.12 g) and sodium alginate (0.6 g, 0.8 g and 1 g) as viscosity enhancer were added in the formulation; 9 formulations were prepared according to 32 factorial designs and evaluated. The responses were analyzed for the analysis of variance using Design-Expert version 10 software. Statistical models were generated for each response parameter. Results: Optimized formulation batch F7 (0.12% gelrite and 0.6% sodium alginate) was liquid before addition of simulated tear fluid (STF) and underwent rapid gelation on addition of STF and had given 84.05% cumulative drug release; the formulation was found to be clear, having good in situ gelling capacity, good antibacterial efficacy, having drug content 99.75%; optimized formulation was sterile and showed sustained drug release over 8 h period as compared to marketed eye drop. Conclusions: From the above results, we can concluded that 32 full factorial design and statistical models can be successfully used to optimize the formulations, and it was concluded that the trial batch F7 (0.12% gelrite and 0.6% sodium alginate) is the best formula (percentage cumulative drug release over 84.05%) and it is possible to formulate in situ ophthalmic gels of MOX HCL using gelrite in combination with sodium alginate for the treatment of various bacterial infections of the eyes.